Electrolyte and lithium battery

CN123018126APending Publication Date: 2026-10-30ENVISION AESC JAPAN LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113469.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0014]从上面所述可以看出,本公开提供的一种电解液及锂电池,其中,所述电解液包括第一添加剂和第二添加剂;所述第一添加剂为如下式(I)所示的化合物:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018126A_ABST
    Figure CN123018126A_ABST
Patent Text Reader

Abstract

The present disclosure provides an electrolyte and a lithium battery. Specifically, the electrolyte comprises a first additive and a second additive; the first additive is a compound represented by formula (I): formula (I); in formula (I), R is independently selected from any one of hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, and substituted or unsubstituted 3- to 8-membered heterocyclic group; and the second additive is lithium difluoro(oxalato)borate. By adding the first additive and the second additive in the electrolyte, a uniform, stable and high-ionic-conductivity protective film can be formed at the electrode-electrolyte interface, thereby improving the performance of the battery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of battery technology, and more particularly to an electrolyte and a lithium battery. Background Technology

[0002] In recent years, the explosive growth of the new energy vehicle market has driven the rapid expansion of the secondary alkali metal ion battery industry. However, as the energy density of commercial batteries gradually approaches its theoretical limit, breaking through the performance bottleneck of high energy density systems under wide temperature range conditions has become the key to alleviating range anxiety and achieving all-climate adaptability. Summary of the Invention

[0003] In view of this, the purpose of this disclosure is to provide an electrolyte and a lithium battery.

[0004] To achieve the above objectives, in a first aspect, this disclosure provides an electrolyte, wherein the electrolyte comprises a first additive and a second additive; wherein... The first additive is a compound represented by the following formula (I): Formula (I); In formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, and substituted or unsubstituted heterocyclic group from 3 to 8 members; when substituted, the substituent is selected from at least one of halogen, amino, cyano or silyl. The second additive is lithium difluorooxalate borate.

[0005] In some embodiments, the heterocyclic group is selected from pyridine, cyclic carboxylic anhydrides, or imidazole; and / or The mass ratio of the first additive to the second additive is 5:1 to 5:12.

[0006] In some embodiments, the compound represented by formula (I) comprises at least one of the following structural formulas: Formula (I-1), Formula (I-2), Formula (I-3), Formula (I-4).

[0007] In some embodiments, based on the total mass of the electrolyte, the mass fraction of the first additive is 0.1% to 2%, and the mass fraction of the second additive is 0.1% to 2%.

[0008] In some embodiments, based on the total mass of the electrolyte, the mass fraction of the first additive is 0.3% to 1%, and the mass fraction of the second additive is 0.5% to 1%.

[0009] In some embodiments, lithium bis(oxalato)borate is further included; the mass fraction of lithium bis(oxalato)borate is 0.1% to 1% based on the total mass of the electrolyte.

[0010] In some embodiments, the electrolyte further includes a solvent; the solvent includes at least one of fluoroethylene carbonate, difluoroethylene carbonate, fluoroethyl methyl carbonate, 2,2-difluoroethyl acetate, and diethyl 2,2-difluorocarbonate. and / or The electrolyte further includes a lithium salt; the lithium salt includes at least one of lithium hexafluorophosphate and lithium difluorosulfonylimide.

[0011] In some embodiments, the mass fraction of the ethyl methyl fluorocarbonate is 40% to 70% based on the total mass of the electrolyte; and / or Based on the total mass of the electrolyte, the mass fraction of the lithium salt is 10% to 20%.

[0012] Secondly, embodiments of this disclosure provide a lithium battery, including a positive electrode, a negative electrode, and any of the aforementioned electrolytes.

[0013] In some embodiments, the positive electrode includes a positive electrode active material, which includes at least one of lithium nickel manganese oxide and a ternary positive electrode material; in the ternary positive electrode material, the mass percentage of nickel is not less than 80% based on the total mass of metal elements other than lithium.

[0014] As can be seen from the above, the present disclosure provides an electrolyte and a lithium battery, wherein the electrolyte includes a first additive and a second additive; the first additive is a compound represented by the following formula (I): Formula (I); in Formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, or substituted or unsubstituted 3- to 8-membered heterocyclic group; when substituted, the substituent is selected from at least one of halogen, amino, cyano, or silyl; the second additive is lithium difluorooxalate borate. By adding the first and second additives to the electrolyte, a uniform, stable, and highly ion-conducting protective film can be formed at the electrode-electrolyte interface, which can effectively improve the interfacial kinetics of the electrolyte while ensuring good high-temperature stability of the electrolyte, thereby improving the performance of the battery system. Detailed Implementation

[0015] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments.

[0016] It should be noted that, unless otherwise defined, the technical or scientific terms used in the embodiments of this disclosure should have the ordinary meaning as understood by one of ordinary skill in the art to which this disclosure pertains.

[0017] In this disclosure, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this document, and "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12.

[0018] Unless otherwise specified, all embodiments and optional embodiments of this disclosure can be combined to form new technical solutions.

[0019] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions.

[0020] Unless otherwise specified, the terms "comprising" and "including" as used in this disclosure can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0021] Unless otherwise specified, the term "or" is inclusive in this disclosure. For example, the phrase "A or B" means "A, B, or both A and B".

[0022] Terminology Explanation A solid electrolyte interface (SEI) is a passivation layer formed on the surface of the electrode material during the charging and discharging process of a lithium-ion battery, resulting from the reaction between the electrode material and the electrolyte at the solid-liquid interface. In some cases, it can specifically refer to the passivation layer located on the surface of the negative electrode. This passivation layer is an interface layer, exhibiting characteristics of a solid electrolyte; it is an electronic insulator but is actually a lithium electrolyte. + Li is an excellent conductor. + It can freely embed and extract through this passivation layer.

[0023] The cathode electrolyte interface (CEI) is an interface film formed on the surface of the positive electrode of a lithium battery. When the positive electrode material is at a high potential, it undergoes an oxidation reaction with the electrolyte, thereby forming an interface layer between the two, which has the function of preventing the electrolyte from continuously oxidizing under high voltage.

[0024] Direct current internal resistance (DCR) is the equivalent internal resistance of a battery under DC operating conditions. It reflects the battery's ability to impede DC current and can characterize the battery's dynamic performance. It is one of the important indicators of whether a battery can achieve long-term cycling.

[0025] Currently, high energy density systems are mainly developing along two technological paths: one is the "high-capacity system" represented by high-nickel ternary batteries paired with high-silicon anodes (Ni-rich / Si), which, with its ultra-high specific capacity advantage, has taken the lead in pushing the energy density of single cells to the 300Wh / kg level; the other is the "high-voltage system" represented by high-voltage cobalt-free lithium nickel manganese oxide (LNMO), which relies on 4.7V (vs. Li) + The ultra-high discharge platform of Li can achieve an energy density of >250Wh / kg when combined with a graphite anode.

[0026] While the aforementioned systems exhibit superior specific energy at room temperature, they still have significant shortcomings for wide-temperature-range applications: high-capacity systems, despite their leading energy density, suffer from insufficient high-temperature thermal stability due to highly active interfaces; high-voltage systems, while possessing intrinsic safety and cost advantages, experience exacerbated high-voltage interfacial side reactions at high temperatures and face the challenge of electrolyte kinetic stagnation under extremely cold conditions. Therefore, the core challenge in realizing the practical application of high-specific-energy-density power batteries across a wide temperature range lies in how to synergistically improve the battery's thermal safety at high temperatures and ion transport efficiency at low temperatures while maintaining high energy density.

[0027] In related technologies, commonly used high-voltage electrolyte systems generally suffer from a significant "performance gap across a wide temperature range": on the one hand, conventional oxidation-resistant formulations used to meet the requirements of highly reactive cathodes often lead to violent reduction side reactions at the anode interface at high temperatures, resulting in a surge in interfacial DCR and accelerated capacity decay, severely restricting the stability of the battery's high-temperature cycling; on the other hand, such systems are limited at low temperatures by increased electrolyte viscosity and insufficient lithium salt dissociation, leading to a sharp drop in ionic conductivity and a dramatic increase in charge transfer impedance, resulting in a severe deterioration in the battery's low-temperature discharge capacity and fast-charging performance. Therefore, the electrolytes provided by related technologies struggle to overcome the technical bottleneck of balancing high-energy-density systems with high-temperature storage / cycling and low-temperature kinetics.

[0028] In view of this, the present disclosure provides an electrolyte and a lithium battery. Specifically, the electrolyte includes a first additive and a second additive; the first additive is a compound represented by the following formula (I): Formula (I); in Formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, or substituted or unsubstituted 3- to 8-membered heterocyclic group; when substituted, the substituent is selected from at least one of halogen, amino, cyano, or silyl; the second additive is lithium difluorooxalate borate. By adding the first and second additives to the electrolyte, a uniform, stable, and highly ion-conducting protective film can be formed at the electrode-electrolyte interface, which can effectively improve the interfacial kinetics of the electrolyte while ensuring good high-temperature stability of the electrolyte, thereby improving the performance of the battery system.

[0029] To make the technical solutions of this disclosure clearer and easier to understand, the electrolyte and lithium battery provided in this disclosure will be described in detail below with reference to specific embodiments.

[0030] electrolyte In some embodiments, the electrolyte includes a first additive and a second additive; wherein the first additive is a compound represented by formula (I): Formula (I); in Formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, substituted or unsubstituted heterocyclic group from 3 to 8 members; when substituted, the substituent is selected from at least one of halogen, amino, cyano or silyl; the second additive is lithium difluorooxalatoborate (LiDFOB).

[0031] For example, the halogen can be F, Cl, Br, etc. The substituted or unsubstituted amino group can be amino, dimethylamino, diethylamino, etc. The silyl group can be trimethylsilyl, etc. The unsubstituted alkyl group can be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, etc. The unsubstituted alkenyl group can be vinyl, propenyl, butenyl, etc. The unsubstituted alkynyl group can be ethynyl, butynyl, etc. The group containing an ester group can be methyl ester, ethyl ester, acetoxy, etc. The group containing a carbonyl group can be formaldehyde, acetaldehyde, acetone, etc. The heterocyclic group can be pyrazole, furan, piperidine, aziridine, pyridine, cyclic carboxylic anhydride, imidazole, etc.

[0032] Optionally, the compound represented by formula (I) includes at least one of the following structural formulas: Formula (I-1), Formula (I-2), Formula (I-3), Formula (I-4).

[0033] In the aforementioned electrolyte, the second additive preferentially decomposes to form a rigid inorganic substrate. The second additive or its decomposition intermediates can undergo strong coordination or hydrogen bonding with the polar functional groups in the first additive, causing them to be directionally adsorbed and enriched on the inorganic phase. Subsequently, the first additive polymerizes to form C=O-containing organic substances that are uniformly embedded in the inorganic bottom layer, thus forming a composite interface phase that combines rigidity and flexibility. In addition, the first additive can chelate transition metals dissolved from the positive electrode side, which can simultaneously improve high-temperature cycling stability and low-temperature discharge performance.

[0034] It can be seen that, through the synergistic effect of the first and second additives, organic-inorganic composite interfaces can be constructed at the positive and negative electrodes respectively. These composite interfaces can take into account toughness, high ionic conductivity, and mechanical strength. Combined with the chelating effect of the first additive, it can improve the technical problems of transition metal dissolution, instability of the positive and negative electrode interfaces, and difficulty in achieving both wide-temperature performance in high-energy-density systems, and achieve the technical effect of significantly suppressing interfacial side reactions and improving high and low temperature performance.

[0035] In some embodiments, the mass fraction of the first additive, based on the total mass of the electrolyte, is 0.1% to 2%, for example, 0.1%, 0.18%, 0.3%, 0.5%, 0.75%, 1%, 1.3%, 1.5%, 1.8%, 2%, etc. Optionally, the mass fraction of the first additive, based on the total mass of the electrolyte, is 0.3% to 1%, for example, 0.3%, 0.4%, 0.55%, 0.75%, 0.9%, or 1%, etc. Lithium batteries prepared with such a mass fraction of the first additive exhibit superior performance.

[0036] In some embodiments, the mass fraction of the second additive is 0.1% to 2% based on the total mass of the electrolyte, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 1.25%, 1.5%, 2%, etc. Optionally, the mass fraction of the second additive is 0.5% to 1% based on the total mass of the electrolyte, for example, 0.5%, 0.75%, 0.9%, or 1%, etc. Lithium batteries prepared with such a mass fraction of the second additive exhibit superior performance.

[0037] In some embodiments, the mass ratio of the first additive to the second additive is 5:1 to 5:12, for example, 5:1, 4:1, 3:1, 2:1, 1:1, 1:1.8, 1:2, or 5:12. Using such a range of ratios, lithium batteries exhibit lower initial impedance and better low-temperature and high-temperature cycle stability.

[0038] In some embodiments, the electrolyte further includes lithium bis(oxalato)borate (LiBOB); based on the total mass of the electrolyte, the mass fraction of lithium bis(oxalato)borate is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, etc. It should be noted that lithium bis(oxalato)borate can synergistically work with the first additive and the second additive to further improve battery performance.

[0039] In some embodiments, the solvent is further included; the solvent includes at least one of fluoroethylene carbonate (FEC), difluoroethylene carbonate, fluoroethyl methyl carbonate (FEMC), 2,2-difluoroethyl acetate, and 2,2-difluorocarbonate diethyl ester.

[0040] When the solvent includes a fluorinated solvent, particularly ethyl methyl fluorinated carbonate, the high-voltage cycling stability of the battery is significantly improved. The mechanism may be that the strong electron-withdrawing effect of the fluorinated solvent changes the solvation sheath structure of lithium ions, thereby regulating the timing and kinetics of interfacial film formation, and thus improving the growth quality and uniformity of the interfacial film.

[0041] Furthermore, based on the total mass of the electrolyte, the mass fraction of ethyl methyl fluorocarbonate is 40% to 70%, for example, 45%, 50%, 55%, 60%, 66%, 70%, etc.

[0042] In some embodiments, the electrolyte further includes a lithium salt; the lithium salt includes lithium hexafluorophosphate (LiPF6). Further, based on the total mass of the electrolyte, the mass fraction of lithium hexafluorophosphate is 8% to 20%, for example 8%, 10%, 12%, 15%, 18%, 20%, etc.

[0043] In some embodiments, the lithium salt further includes lithium bisfluorosulfonylimide (LiFSI).

[0044] Furthermore, based on the total mass of the electrolyte, the mass fraction of the lithium salt is 10% to 20%, for example, 10%, 12.5%, 15%, 16%, 18%, 20%, etc. Here, lithium hexafluorophosphate can be used as the first lithium salt, and lithium bis(fluorosulfonyl)imide (LiFSI) can be used as the second lithium salt, with the mass fraction of the first lithium salt being greater than the mass fraction of the second lithium salt.

[0045] In some embodiments, the electrolyte may further comprise vinylene carbonate (VC). Vinylene carbonate helps improve the film-forming performance of the negative electrode.

[0046] lithium batteries This disclosure provides a lithium battery. In some embodiments, the lithium battery includes a positive electrode, a negative electrode, and the aforementioned electrolyte located between the positive and negative electrodes. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes.

[0047] Positive electrode sheet The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0048] For example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0049] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (e.g., polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0050] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese oxide, and ternary cathode materials. For example, the ternary cathode material may be at least one of lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide.

[0051] Optionally, in the ternary cathode material, the mass percentage of nickel is not less than 80%, such as 80% or 90%, based on the total mass of metal elements other than lithium.

[0052] In some embodiments, the positive electrode active material is carbon-coated lithium nickel manganese oxide. The chemical formula of the lithium nickel manganese oxide can be LiaNia. x Mn y O 4-z M z Where 0.90≤a≤1.10, 0.4≤x≤0.6, 1.4≤y≤1.6, 0≤z≤0.1, and element M is one or more of Cl, Br, I, S, Se, Te, or F, such as Li. 1.01 Ni 0.5 Mn 1.5 O 3.9 F 0.1 In the carbon-coated lithium nickel manganese oxide, the mass of the carbon coating layer is 1.0 wt% to 3.0 wt% of the mass of the lithium nickel manganese oxide, for example, 1.5 wt%.

[0053] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0054] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0055] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0056] Negative electrode sheet The negative electrode includes a negative current collector and a film layer optionally disposed on at least one surface of the negative current collector.

[0057] For example, the film layer may include a negative electrode active material, a conductive agent, a thickener, and a binder.

[0058] In some embodiments, the negative electrode active material includes any one or a combination of at least two of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon carbide, or lithium titanate.

[0059] Optionally, the negative electrode active material is graphite.

[0060] In some embodiments, the negative electrode sheet can be prepared by dispersing the negative electrode active material, conductive agent, thickener, binder and any other components in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0061] Separating membrane In some embodiments, the secondary battery further includes a separator. This disclosure does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0062] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0063] Example The following describes embodiments of this disclosure. The embodiments described below are exemplary and are only used to explain this disclosure, and should not be construed as limiting this disclosure. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0064] The specific preparation method of the secondary lithium-ion battery of Embodiment 1 of this disclosure is as follows: (1) Preparation of lithium nickel manganese oxide cathode: Carbon-coated lithium nickel manganese oxide was prepared by the following method: The carbon source is pre-sintered to obtain component B; component B is mixed with lithium nickel manganese oxide and sintered again to obtain carbon-coated lithium nickel manganese oxide, wherein component B accounts for 0.5% to 4% of the total mass.

[0065] Here, the carbon source can be one or more of fructose, polyethylene glycol, galactose, polyvinylpyrrolidone, and tannic acid, such as tannic acid. In this embodiment, tannic acid is used as the carbon source.

[0066] The pre-sintering temperature can be 500℃~650℃, for example 520℃. In this embodiment, the pre-sintering temperature is 520℃.

[0067] The pre-sintering time can be 3 hours to 6 hours, for example, 4 hours. In this embodiment, the pre-sintering time is 4 hours.

[0068] The secondary sintering temperature can be 400℃~500℃, for example 420℃. In this embodiment, the secondary sintering temperature is 420℃.

[0069] The secondary sintering time can be 14h to 18h, for example, 16h. In this embodiment, the secondary sintering time is 16h.

[0070] The positive electrode active material prepared above, polyvinylidene fluoride as a binder, and Super P as a conductive agent are mixed in a weight ratio of 98:1:1. N-methylpyrrolidone (NMP) is added and the mixture is stirred evenly under vacuum to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated onto an aluminum foil. After the aluminum foil is dried at room temperature, it is transferred to an oven for drying. Then, it is cold-pressed and slit to obtain the positive electrode (electrode sheet).

[0071] (2) Preparation of graphite anode: Graphite was used as the negative electrode active material, Super P as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) as the thickener, and styrene-butadiene rubber (SBR) as the binder. They were mixed in a mass ratio of 96:1:1:2, and deionized water was added. The mixture was stirred in a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry was uniformly coated onto the negative electrode current collector copper foil. After the copper foil was dried at room temperature, it was transferred to an oven for drying. Then, it was cold-pressed and slit to obtain the negative electrode (electrode sheet).

[0072] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10ppm, the solvent, lithium salt, and additives were prepared according to the mass ratios in Table 1 to obtain the electrolyte (i.e., Example 1 in Table 1).

[0073] In Table 1, the content of each component is a weight percentage calculated based on the total weight of the electrolyte. In other examples and comparative examples, the electrolytes are prepared in the same way as in this example, except that the component ratios are not specified in Table 1. Where the content of each component in the table is less than 100%, dimethyl carbonate (DMC) is used to make up the difference.

[0074] (4) Preparation of the separating membrane: Polypropylene film is used as the separator.

[0075] (5) Preparation of secondary batteries: The positive electrode, separator, and negative electrode obtained above are stacked sequentially, with the separator positioned between the positive and negative electrodes to provide isolation. Then, an aluminum-plastic film is wrapped around the separator, and the mixture is dried in a vacuum oven at 120°C. After injecting 3.0 g / Ah of electrolyte, the mixture is sealed. Following processes such as settling, hot and cold pressing, formation, clamping, and capacity testing, a 1Ah soft-pack battery (i.e., a lithium-ion battery) is finally produced.

[0076] Example 18 and Comparative Example 8 The difference between Example 18 and Example 1 is that the positive electrode active material is lithium cobalt oxide. The difference between Comparative Example 8 and Comparative Example 2 is that the positive electrode active material is lithium cobalt oxide.

[0077] Example 19 and Comparative Example 9 The difference between Example 19 and Example 1 is that the positive electrode active material is a ternary positive electrode material; specifically, in this example, it is lithium nickel cobalt manganese oxide (LiNi). 0.9 Co 0.05 Mn 0.05 O2. The difference between Comparative Example 9 and Comparative Example 2 is that the positive electrode active material is lithium nickel cobalt manganese oxide.

[0078] Example 24 and Comparative Example 7 The difference between Example 24 and Example 1 is that the positive electrode active material is uncoated lithium nickel manganese oxide; the difference between Comparative Example 7 and Comparative Example 1 is that the positive electrode active material is uncoated lithium nickel manganese oxide.

[0079] It should be noted that, unless otherwise specified, the positive electrode active materials in the other embodiments and comparative examples are the same as those in Example 1.

[0080] Test methods The secondary batteries prepared in the above embodiments and comparative examples can be tested using the following methods, and the results are shown in Table 2.

[0081] (1) DC resistance (DCR) test of secondary battery At 25°C, the lithium-ion battery was charged and discharged twice at 0.33C, and the discharge capacity of the last charge cycle was taken as the battery's rated capacity. Then, the battery was discharged at 0.33C to 50% SOC (state of charge, reflecting the battery's remaining capacity), and the current was increased to 1C and held for 30 seconds. The difference between the updated stable voltage and the original plateau voltage was measured, and the ratio of this difference to the 1C current value is the battery's DC resistance.

[0082] (2) Capacity retention rate during 10℃ low-temperature cycling At 25℃, the lithium-ion battery was charged and discharged twice at 0.33C, and the discharge capacity of the last charge / discharge cycle was taken as the battery's rated capacity. The ambient temperature was adjusted to 10℃, and the battery was allowed to stand for 1 hour. It was then charged at 0.5C to the cutoff voltage, kept constant at 0.05C, and discharged at 1C to the cutoff voltage, for a total of 500 cycles. The capacity retention rate after 500 cycles at 10℃ was calculated using the following formula: Low-temperature cycling capacity retention (%) = (discharge capacity at 500th cycle / discharge capacity at 1st cycle) × 100%.

[0083] (3) Capacity retention and DCR growth rate at 45℃ high temperature cycling At 25℃, the battery was charged and discharged three times at 0.33C within the specified voltage range. The capacity of the last discharge was recorded as the battery's rated capacity, and the initial discharge rate (DCR) was measured and recorded as DCR0. The cell was then placed in a 45℃ constant temperature chamber and cycled 500 times at 1C / 1C within the specified voltage range. After cycling, the cell was cooled to 25℃, and the discharge capacity corresponding to the 500th cycle was recorded. The DCR after cycling was measured and recorded as DCR0. 500 .

[0084] Capacity retention rate (%) after 500 cycles at 45℃ = (Discharge capacity on the 500th cycle / Discharge capacity on the 1st cycle) × 100%; DCR growth rate (%) = [(DCR)] 500 —DCR0) / DCR0]×100%.

[0085] Where C0 is the discharge capacity before the cycle, C 500 The discharge capacity is denoted as DCR0 after 500 cycles at 45°C, where DCR0 is the initial DCR before cycling. 500 The DCR is the result of 500 cycles at 45°C.

[0086] For lithium nickel manganese oxide / graphite batteries, the operating voltage range is 3.4 V ~ 4.85 V.

[0087] For lithium cobalt oxide / graphite batteries, the operating voltage range is 2.5V~4.45V.

[0088] For lithium nickel manganese cobalt oxide / graphite batteries, the operating voltage range is 2.5V~4.25V.

[0089] Table 1. Electrolyte composition of different groups of examples and comparative examples

[0090] Table 2 Performance test results of different groups of examples and comparative examples

[0091] Comparing Comparative Examples 1 to 4 and Example 1, it can be seen that for lithium-ion batteries using carbon-coated lithium nickel manganese oxide positive electrode active material, the high-temperature performance of lithium-ion batteries can be significantly improved under the synergistic effect of the first additive and the second additive.

[0092] Comparing Comparative Example 7 and Example 24, it can be seen that for lithium-ion batteries using uncoated lithium nickel manganese oxide positive electrode active material, the performance of lithium-ion batteries can be improved under the synergistic effect of the first and second additives, especially the high-temperature performance is greatly improved.

[0093] Comparing Comparative Example 8 and Example 18, it can be seen that for lithium-ion batteries using lithium cobalt oxide positive electrode active material, adding the first additive and the second additive can also improve the performance of lithium-ion batteries compared to adding vinylene carbonate.

[0094] Comparing Comparative Example 9 and Example 19, it can be seen that for lithium-ion batteries using lithium nickel cobalt manganese oxide positive electrode active material, adding the first additive and the second additive can also improve the performance of lithium-ion batteries, especially the high-temperature performance.

[0095] Therefore, the synergistic effect of the first and second additives can effectively improve the high-temperature performance of lithium-ion batteries prepared from various cathode active materials. The mechanism of this synergistic effect may be that the second additive preferentially decomposes to form a rigid inorganic substrate. The second additive or its decomposition intermediates can undergo strong coordination or hydrogen bonding with the polar functional groups in the first additive, causing them to be directionally adsorbed and enriched on the inorganic phase. Subsequently, the first additive polymerizes to form C=O-containing organic matter and uniformly embeds it into the inorganic bottom layer, thus forming a composite interface phase that combines rigidity and flexibility. This composite interface can balance toughness, high ionic conductivity, and mechanical strength. Furthermore, the chelating effect of the first additive can improve the inhibition of interfacial side reactions during transition metal dissolution in high-energy-density systems.

[0096] Comparing Examples 1 to 5, it can be seen that increasing the amount of the first additive while keeping the amount of the second additive constant can improve the performance of the lithium-ion battery. Further increasing the amount of the first additive reduces the improvement in performance. Specifically, when the amount of the first additive is in the range of 0.3% to 1%, the overall performance of the lithium-ion battery is better.

[0097] Comparing Comparative Example 1, Comparative Example 2, Example 1, and Examples 6 to 8, it can be seen that different types of first additives all have an improving effect on the performance of lithium-ion batteries.

[0098] Comparing Examples 1 and 9-12, it can be seen that, while keeping the amount of the first additive constant, increasing the amount of the second additive results in a trend where the cycle capacity retention of the lithium-ion battery first increases and then decreases, while the cycle DCR first decreases and then increases. Specifically, the amount of the second additive within the range of 0.1% to 1.5% can improve the overall performance of the lithium-ion battery.

[0099] Comparative Examples 1 and 4, and 11 and 5, show that adding both the first and second additives simultaneously significantly improves the performance of lithium-ion batteries compared to adding the second additive alone. Adding a suitable proportion of the first additive when the amount of the second additive is large (e.g., 1.2%) can also improve the performance of lithium-ion batteries.

[0100] Comparing Comparative Example 6 and Example 17, it can be seen that adding the first additive and the second additive can improve the cycle performance of lithium-ion batteries when the solvent does not contain FEMC. Comparing Examples 14 to 17, it can be seen that adding FEMC to the solvent while keeping the amounts of the first additive and the second additive constant helps to improve the cycle performance of lithium-ion batteries.

[0101] Comparing Examples 1 and 20-23, it can be seen that adding LiBOB to the solution helps to further improve the overall performance of lithium-ion batteries.

[0102] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of this disclosure (including the claims) is limited to these examples; within the framework of this disclosure, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of the embodiments of this disclosure as described above, which are not provided in detail for the sake of brevity.

[0103] This disclosure is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the scope of protection of this disclosure.

Claims

1. An electrolyte, characterized in that, The electrolyte includes a first additive and a second additive; wherein... The first additive is a compound represented by the following formula (I): Equation (I); In formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, and substituted or unsubstituted heterocyclic group from 3 to 8 members; when substituted, the substituent is selected from at least one of halogen, amino, cyano or silyl. The second additive is lithium difluorooxalate borate.

2. The electrolyte according to claim 1, characterized in that, The heterocyclic group is selected from pyridine, cyclic carboxylic anhydride, or imidazole; and / or The mass ratio of the first additive to the second additive is 5:1 to 5:

12.

3. The electrolyte according to claim 1, characterized in that, The compound represented by formula (I) includes at least one of the following structural formulas: Equation (I-1), Equation (I-2), Equation (I-3), Equation (I-4).

4. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass fraction of the first additive is 0.1% to 2%, and the mass fraction of the second additive is 0.1% to 2%.

5. The electrolyte according to claim 4, characterized in that, Based on the total mass of the electrolyte, the mass fraction of the first additive is 0.3% to 1%, and the mass fraction of the second additive is 0.5% to 1%.

6. The electrolyte according to claim 1, characterized in that, It also includes lithium bis(oxalato)borate; the mass fraction of the lithium bis(oxalato)borate is 0.1% to 1% based on the total mass of the electrolyte.

7. The electrolyte according to claim 1, characterized in that, The electrolyte further includes a solvent; the solvent includes at least one of fluoroethylene carbonate, difluoroethylene carbonate, fluoroethyl methyl carbonate, 2,2-difluoroethyl acetate, and 2,2-difluorocarbonate. and / or The electrolyte further includes a lithium salt; the lithium salt includes at least one of lithium hexafluorophosphate and lithium difluorosulfonylimide.

8. The electrolyte according to claim 7, characterized in that, Based on the total mass of the electrolyte, the mass fraction of the ethyl methyl fluorocarbonate is 40% to 70%; and / or Based on the total mass of the electrolyte, the mass fraction of the lithium salt is 10% to 20%.

9. A lithium battery, comprising a positive electrode, a negative electrode, and an electrolyte according to any one of claims 1 to 8.

10. The lithium battery according to claim 9, characterized in that, The positive electrode includes a positive electrode active material, which includes at least one of lithium nickel manganese oxide and a ternary positive electrode material; in the ternary positive electrode material, the mass percentage of nickel is not less than 80% based on the total mass of metal elements other than lithium.